HIF-independent synthetic lethality between CDK4/6 inhibition and VHL loss across species. - Nicholson, H.E.; Tariq, Z.; Housden, B.E.; Jennings, R.B.; Stransky, L.A.; Perrimon, N.; Signoretti, S.; Kaelin, W.G. (Science signaling, 2019)
Inactivation of the VHL tumor suppressor gene is the signature initiating event in clear cell renal cell carcinoma (ccRCC), the most common form of kidney cancer, and causes the accumulation of hypoxia-inducible factor 2? (HIF-2?). HIF-2? inhibitors are effective in some ccRCC cases, but both de novo and acquired resistance have been observed in the laboratory and in the clinic. Here, we identified synthetic lethality between decreased activity of cyclin-dependent kinases 4 and 6 (CDK4/6) and VHL inactivation in two species (human and Drosophila) and across diverse human ccRCC cell lines in culture and xenografts. Although HIF-2? transcriptionally induced the CDK4/6 partner cyclin D1, HIF-2? was not required for the increased CDK4/6 requirement of VHL-/- ccRCC cells. Accordingly, the antiproliferative effects of CDK4/6 inhibition were synergistic with HIF-2? inhibition in HIF-2?-dependent VHL-/- ccRCC cells and not antagonistic with HIF-2? inhibition in HIF-2?-independent cells. These findings support testing CDK4/6 inhibitors as treatments for ccRCC, alone and in combination with HIF-2? inhibitors.